Distribution of brain sodium long and short relaxation times and concentrations: a multi-echo ultra-high field 23Na MRI study - Ridley, Ben; Nagel, Armin Michael; Bydder, Mark; Maarouf, Adil; Stellmann, Jan-Patrick; Gherib, Soraya; Verneuil, Jeremy; Viout, Patrick; Guye, Maxime; Ranjeva, Jean-Philippe; Zaaraoui, Wafaa (Scientific Reports, 2018)
Sodium (23Na) MRI proffers the possibility of novel information for neurological research but also particular challenges. Uncertainty can arise in in vivo 23Na estimates from signal losses given the rapidity of T2* decay due to biexponential relaxation with both short (T2*short) and long (T2*long) components. We build on previous work by characterising the decay curve directly via multi-echo imaging at 7 T in 13 controls with the requisite number, distribution and range to assess the distribution of both in vivo T2*short and T2*long and in variation between grey and white matter, and subregions. By modelling the relationship between signal and reference concentration and applying it to in vivo 23Na-MRI signal, 23Na concentrations and apparent transverse relaxation times of different brain regions were measured for the first time. Relaxation components and concentrations differed substantially between regions of differing tissue composition, suggesting sensitivity of multi-echo 23Na-MRI toward features of tissue composition. As such, these results raise the prospect of multi-echo 23Na-MRI as an adjunct source of information on biochemical mechanisms in both physiological and pathophysiological states.
EVALuna2:36260